A case of receipt in Peru: The legal incapacity of amazonian people in the Brazilian Civil Code - Ramos Núñez, Carlos (2018)
An important and lengthy debate took place in Peru, in the twenties, when the Civil Code of 1936 was elaborated, regarding the legal capacity of indigenous peoples. The third paragraph of the article six of the Brazilian Civil Code of 1916, which declared that Amazonian persons had relative legal incapacity, led to a debate in Peru that lasted for years. Those who championed the inclusion of a similar approach in the Peruvian Civil Code sought to protect the natives, who, in their view, were in disadvantage in modern society because of their lack of education. In the final version of the code, it was decided not to include that rule and to maintain the criteria of formal and artificial equality regarding the legal capacity of the natives, mainly because otherwise was even more harmful for them. However, a protectionist sentiment remained in the political and cultural discourse.